2006
DOI: 10.1007/s10719-006-9008-x
|View full text |Cite
|
Sign up to set email alerts
|

The human serotonin1A receptor exhibits G-protein-dependent cell surface dynamics

Abstract: Seven transmembrane domain G-protein-coupled receptors constitute the largest family of proteins in mammals. Signal transduction events mediated by such receptors are the primary means by which cells communicate with and respond to their external environment. The major paradigm in this signal transduction process is that stimulation of the receptor leads to the recruitment and activation of heterotrimeric GTP-binding proteins. These initial events, which are fundamental to all types of G-protein-coupled recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…In addition, the percentage of the mobile fraction is very high (Ͼ85%) in the three cellular compartments studied. The diffusion characteristics of the sst 2A is similar from those reported for other GPCRs in extrasynaptic sites, such as the serotonin 5HT 1A (Pucadyil and Chattopadhyay, 2007) and dopamine D 1 (Scott et al, 2006) receptors. In spines, although the sst 2A receptor has been shown to potentially interact with scaffolding proteins of the postsynaptic density Shank1 and ProSAP1/CortBP1 (Zitzer et al, 1999a,b), our results indicate that, in resting conditions, only a minor portion of sst 2A receptors might be associated with cytoskeletal anchoring proteins.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, the percentage of the mobile fraction is very high (Ͼ85%) in the three cellular compartments studied. The diffusion characteristics of the sst 2A is similar from those reported for other GPCRs in extrasynaptic sites, such as the serotonin 5HT 1A (Pucadyil and Chattopadhyay, 2007) and dopamine D 1 (Scott et al, 2006) receptors. In spines, although the sst 2A receptor has been shown to potentially interact with scaffolding proteins of the postsynaptic density Shank1 and ProSAP1/CortBP1 (Zitzer et al, 1999a,b), our results indicate that, in resting conditions, only a minor portion of sst 2A receptors might be associated with cytoskeletal anchoring proteins.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, the GABA A receptor has been shown to diffuse rapidly within the extrasynaptic membrane (28). Rapid diffusion is not restricted to receptor ion channels, as the G-protein-coupled serotonin 5-HT1a (29) and dopamine D1 (30) receptors also move freely in extrasynaptic membrane. Taken together, the data indicate that GABA B receptors exhibit distinctive diffusion dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated whether stimulation of GABA B might affect receptor movement, as previous studies have demonstrated that movement of other metabotropic receptors, such as the serotonin 5-HT1a receptor, is greater following agonist stimulation (29,34). We treated cells expressing GABA B1 and GABA B2 with the agonist baclofen and found that baclofen stimulation significantly increased its diffusion rate; the effect of baclofen was prevented by co-treatment with a GABA B antagonist.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, stimulation by serotonin has not been found to result in any significant difference in the fluorescence distribution of serotonin 1A receptor fused to EYFP ). However, a significant increase in the lateral mobility of the serotonin 1A receptor fused to EYFP has been shown using fluorescence recovery after photobleaching (FRAP) Pucadyil and Chattopadhyay 2007c). Based on all these results, it appears that while the membrane dynamics (diffusion) of the serotonin 1A receptor could be modulated in the presence of serotonin, fluorescence distribution and detergent insolubility measurements do not indicate any apparent cell surface reorganization of the receptor when stimulated by serotonin.…”
Section: Monitoring Membrane Organization Of the Serotonin 1a Receptomentioning
confidence: 96%